Prevalence of OATP1B‐Mediated Drug–Drug Interactions in an Academic Medical Center - Mathilde Bories; David Malnoë; Pascal Le Corre (Clinical and Translational Science, 2025)
ABSTRACT OATP1B is a key transporter involved in hepatic drug uptake, where its inhibition can significantly increase plasma drug levels, leading to potential adverse effects. This retrospective study aimed to determine the prevalence of potential drug–drug interactions (pDDIs) mediated by the hepatic transporter OATP1B1/3 in a cohort of 44,877 patients hospitalized at Rennes Academic Medical Center, using data from the Clinical Data Warehouse. We analyzed prescription rates of OATP1B substrates and inhibitors and estimated the prevalence of pDDIs, assessed the consistency of pDDI identification across different drug interaction databases, and performed a literature review of identified OATP1B‐based pDDIs. The identification of pDDIs across different drug databases showed inconsistencies, with limited overlap and variability in reported interactions. Among hospitalized patients, 6954 (15.5%) received OATP1B substrates, while 408 (0.9%) received inhibitors, leading to 106 pDDIs observed in 99 patients (0.2%). The pDDI rate varied significantly depending on the inhibitor used, reaching up to 39.1% in patients treated with ciclosporin. Statins accounted for a large proportion of pDDIs, emphasizing the potential risks, especially in multidrug regimens. Commonly involved inhibitors included FDA drugs such as ciclosporin, clarithromycin, and rifampicin. The clinical relevance of these interactions remains uncertain due to the limited availability of supporting evidence and the restricted list of well‐characterized OATP1B substrates and inhibitors. This study highlights the complexity of OATP1B‐mediated pDDIs and the need for increased clinical awareness and further research to improve the detection and characterization of such pDDIs, particularly for high‐risk drugs with a narrow therapeutic index.